Restorative Proctocolectomy and Ileal Pouch-anal Anastomosis. Issue 5 (November 2015) - Parc, Yann; Reboul-Marty, Jeanne; Lefevre, Jeremie H.; Shields, Conor; Chafai, Najim; Tiret, Emmanuel
Abstract : Objectives: To assess mortality after restorative proctocolectomy (RPC) and determine the influencing factors with a specific focus on institutional caseload and surgical approach in France. Background: RPC is an uncommonly performed and demanding procedure; case volume may exert a significant influence on outcome. Methods: Data of all patients who underwent RPC in France between 2009 and 2012, including demographics, diagnosis, procedures, mode of admission, discharge, and hospital type were collected. Results: One thousand one hundred sixty-six RPCs were performed in 237 centers (mean: 1.65 procedure/year/center). Rate of laparoscopic procedures was 47.1% (n = 549). Mortality reached 1.5% (n = 17). Independent factors for mortality were ageless than 45 years (odds ratio, OR = 3.9) and surgery in a center performing less than 3 RPC per year (OR = 3.2). Centers performing less than 3 RPC per year represented 89% of all centers, accounted for 37% (n = 431) of all patients and represented 70.6% of all deaths (n = 12). Underlying pathology exerted a significant effect on mortality; mortality rate after "classical" indications (polyposis and inflammatory bowel disease) was 0.7% (8/1078) and was 16.7% (9/54) for "nonclassical" indications (peritonitis, carcinomatosis, and so on) ( P  < 0.0001). Nonclassical diagnoses were observed more frequently in centers performing less than 3 RPC per year [40/412 (7.3%) vs 24/720 (3.3%), P  = 0.0027]. A laparoscopic approach was associated with a low mortality rate on univariate analysis (0.7% vs 1.2%, P  = 0.05), a shorter hospital stay (15.8 ± 0.6 vs 17.8 ± 0.55, P  = 0.0053) and more frequently performed in experienced centers ≥3 RPC/year (50.8% vs 40.7%, P  = 0.0009). Conclusions: Mortality after RPC in centers performing 3 or less RPC per year was significantly higher, and accounted for more than half of all deaths. In France, consolidating all RPCs to higher volume centers may lead to better outcomes.